Gender, Mobility, and Middle Class in Europe and Central Asia : Insights from Qualitative Research - Petesch, Patti L.; Demarchi, Giorgia (World Bank, Washington, DC, 2015)
New qualitative fieldwork in eight countries of Europe and Central Asia (ECA) indicates that the dramatic declines in poverty in much of the region over the last decade do not appear to be registering very favorably with men and women on the ground. This paper provides a gender analysis of findings from equal numbers of sex-specific focus groups with employed and jobless individuals. The methodology featured a standardized package of semi-structured data collection tools, which enabled systematic comparative analysis of the datasets from 37 urban and rural communities across eight countries in the region. While lack of jobs and the rising cost of living are central concerns for both women and men across the sample, the qualitative data highlights important gender differences in how men and women are responding to these challenges that quantitative survey approaches appear to miss. Throughout the sample, women are widely reported to be doing everything they can to pull their households out of poverty or to maintain their families in the middle class, while men voice deep frustration with their weak economic opportunities and the need for additional household members to contribute economically. Women’s increased economic participation in the face of men’s hardships with breadwinning - and the stress on gender roles and relations that this entails - are crucial for making sense of frustrations on the ground despite the region’s significant social and economic development.